Q Belt / Muhammad Amirul Abdul Kadir … [et al.] - Abdul Kadir, Muhammad Amirul; Harun, Saifullah; Md Hasni, Fazrul Hafifi; Zulkefli, Muhammad Azim Izazi; Samad, Mohd Nizam; Talib, Saharuddin; Ismail, Ilya; Ab Aziz, Ahmad Azlan (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
Most of us know that Qiblah function as guidance to Muslim all over the world to perform solah. But, the truth is Qiblah has other importance beyond solah and plays a part in various ceremonies. The head of an animal that is slaughtered using halal methods is aligned with the Qiblah. After death, Muslims are buried with their heads turned right towards the direction of the Qiblah. Thus, archaeology can indicate Islamic necropolises if no other signs are present. Nowadays, there is a lot of research and invention on finding Qiblah direction, but less of it focusing for blind people, (whereas in this project they will be address as people with disabilities (PWD). Those people facing difficulties to determine the kiblah direction on their own. Referring to the statistic given by Persatuan Pembangunan Orang Buta Malaysia (PPOBM), there are more than 65,000 blind people in Malaysia, whereby 77% are Muslim; but from that figure only around 15,000 registered with PPOBM. Seeing the critical situation, Q-Belt is developed hopefully as a lending hand to solve this problem. When the latitude and longitude data corresponding to the indicator needle on the compass, the belt will vibrate.